Performance of spent garnet as sand replacement in concrete at high temperature - Zulkifli, Ikmal; Mokhatar, Shahrul Niza; Budie, Ahmed Mokhtar Albshir (Penerbit UTHM, 2022)
Garnet is ideal for many commercial uses due to its potential to be recycled. The dumping millions of tons of spent garnet in landfills, quarries, oceans and waterways will cause the creating environmental concerns. In this study, spent garnet as a sand replacement is produced to innovate sustainable concrete. The research objectives are to study the effects of strength of spent garnet as sand replacement in concrete mix at high temperature and to evaluate its physical properties of spent garnet. Several laboratory experiments were conducted to determine the physical and its compressive strength before and after exposed to high temperature. Furthermore, the test for the physical properties that had been conducted were, specific gravity, bulk density and water absorption test. Other than that, the compressive strength of 30MPa at 28 days for trial mix design were prepared accordingly. The cube specimens of 100 × 100 × 100 mm were provided with substitution of 0%, 10%, 20%, 30% and 40% of spent garnet as sand replacement with 0.45 of water cement ration. All the concrete mixes containing spent garnet were produced slump of 30-60mm. Based on the test result, the cube specimen of 40 percent of spent garnet after heated started decrease in term of strength due to the present of the excessive of spent garnet particles in the concrete which can weaken the bond between aggregates and the cement paste. Thus, it reduces the concrete strength in term of less compaction of concrete has lower bonding strength.